Cardiomyogenic Stem and Progenitor Cell Plasticity and the Dissection of Cardiopoiesis - Perino, Maria Grazia (2008)
Cell based therapies hold promise of repairing an injured heart, and the description of stem and progenitor cells with cardiomyogenic potential is critical to its realization. At the vanguard of these efforts are analyses of embryonic stem cells, which clearly have the capacity to generate large numbers of cardiomyocytes in vitro. Through the use of this model system, a number of signaling mechanisms have been worked out that describes at least partially the process of cardiopoiesis. Studies on adult stem and on progenitor cells with cardiomyogenic potential are still in their infancy, and much less is known about the molecular signals that are required to induce the differentiation to cardiomyocytes. It is also unclear whether the pathways are similar or different between embryonic and adult cell-induced cardiomyogenesis, partly because of the continued controversies that surround the stem cell theory of cardiac self-renewal. Irrespective of any perceived or actual limitations, the study of stem and progenitor cells has provided important insights into the process of cardiomyogenesis, and it is likely that future research in this area will turn the promise of repairing an injured heart into a reality.